Governors Matter : A Comparative Study of State-Business Relations in Russia's Regions - Sharafutdinova, Gulnaz; Steinbuks, Jevgenijs (Wiley, 2017)
This study uses the latest 2011 round of the Business Environment and Enterprise Performance Survey for the Russian Federation to take a closer look at regional-level factors influencing the business environment in Russia. Specifically, the study explores the role of regional administrations and variables of administrative continuity and governor origin in shaping regional business environment. The findings reveal that regional businesses in Russia are (1) acutely anxious about administrative transitions (as expressed in gubernatorial replacements) and favor administrative continuity, and (2) favor government officials that are locally embedded. The analysis suggests that many localities in Russia have witnessed the emergence of mutually beneficial state-business arrangements that are inimical to economic competition. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions. http://olabout.wiley.com/WileyCDA/Section/id-820227.html